Sulfur cathodes - Althues, Holger; Dörfler, Susanne; Thieme, Sören; Strubel, Patrick; Kaskel, Stefan (wiley, 2019)
The cathode is a key component affecting the performance of a lithium-sulfur cell. This chapter introduces the components of a lithium-sulfur cathode and their impact on energy density, cycle life, self-discharge, and rate capability. It describes a number of carbon types used to overcome the insulating nature of the active material sulfur including graphite, carbon black, activated carbons, and carbide-derived carbons. These carbons are considered in terms of pore size; micro-, meso-, and macropores and their contribution to controlling the dissolution of lithium polysulfides and areal loading of sulfur in the cathode. The effects of surface modifications and coatings including the properties of binders used in lithium sulfur cathodes are discussed. The contribution of cathode processing methods to cell performance is also discussed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 3D current collector; Carbon blacks; Electrochemical conversion; Lithium polysulfides; Lithium-sulphur cathode; Sulfur impregnation; Sulfur melting diffusion method; Sulfur vaporizing method